MOLECULAR ANALYSIS AND PHYLOGENIC TREE OF SARCOCYSTIS SPECIES ISOLATED FROM SHEEP IN ERBIL PROVINCE- KURDISTAN REGION/ IRAQ - HASSAN, ZUBER ISMAEL (Journal of Duhok University, 2023)
BACKGROUND: A group of cyst-forming parasites known as Sarcocystis species infect both people and animals worldwide. Some of these species affect the host with clinical and subclinical illnesses that can cause financial losses. The diversity and importance of Sarcocystis spp. are poorly studied. METHODS: One hundred ninety tissue sheep samples (esophagus and tongue) were collected from the new Erbil slaughterhouse. The PCR method was used to amplify the 18S ribosomal RNA gene to differentiate Sarcocystis spp. RESULTS: Out of 190 sheep that were examined macroscopically and microscopically using tissue squash preparation, 36.32% were infected with Sarcocystis spp. in Erbil Province. Statistically, there was no significant difference between sexes and the highest rates were found among 1-3 years 40 (57.97%), and the lowest rate of infection was revealed in the less than one year 12 (17.39%) age group. The sequence comparisons showed the highest similarity (99.6-100%) between S. tenella (ON645286- ON645288) obtained from sheep in Erbil Province and S. tenella from Egypt (MG515220) and Iran (MT565493 and KF489419) due to nucleotide changes in the sequences alignments. CONCLUSION: Multiple alignments revealed some differences between the consensus sequences of the isolates identified in this investigation and those of previously published isolates. A phylogenetic analysis of the 18S rRNA gene was used to find new Sarcocystis spp